Pengaruh Keandalan, Ketanggapan Dan Empati Terhadap Kualitas Pelayanan Klinik Bidan Rezki Sinaga Kabupaten Deli Serdang - Chadisa Rizky Ananda; Fauzi Arif Lubis; Nuri Aslami (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the clarity of influence, responsiveness and empathy on the quality of service at the Rezki Sinaga Midwife Clinic. Meanwhile, the research method used is a quantitative method. The population in this study were clinic patients. The number of samples known using the Slovin Formula is 99 respondents. Data collection techniques use questionnaires, documentation studies and observations. Data analysis techniques were analyzed using statistical tools using SPSS. The research results show that the Reliability Variable has a positive and significant effect on Service Quality with a sig value of 0.000 ˂ 0.05 and the t-count > t-table value, namely 19.999 ˃ 1.98525. The Responsiveness variable has a positive and significant effect on Service Quality with a sig value of 0.004 ˂ 0.05 and the t-count > t-table value, namely 2.922 ˃ 1.98525. The Empathy variable has a positive and significant effect on Service Quality with a sig value of 0.000 ˂ 0.05 and the t-count > t-table value, namely 2.254 ˃ 1.98525. The results simultaneously show that there is an influence of noise, responsiveness and empathy which together influence the quality of service, the calculated f value is 261.939 ˃ f-table 2.70 and the Sig value is 0.000 ˂ 0.05. It is recommended for future researchers to involve a larger sample, expand the scope of research, apart from the variables that have been studied, which can also influence service quality.